Transformation of spatial pattern and declining of social capital in Dhaka city , Bangladesh - Sultana, Sheikh Rubaiya (© 2010 BRAC University, 2016)
This article was published in the BRAC University Journal [©2013 Published by Consortia Academia.] and the definite version is available at: http://hdl.handle.net/10361/896